Bioethics of live ans death in seneca´ s throught, sociopolitical reasons for daying - Vargas Vargas, Karla (2021)
Seneca’s thinking is still valid and allows us to explore thematic areas that have been, somehow, relegated; for example, political topics. This article presents a theoretical analysis on the socio-political implications of the way each one: a) leads his life and assumes death as an undeniable part of life itself and, b) values death as an option when the person is no longer useful to the human community. Considering that for Seneca, if a person desires a good death it needs to be preceded by good life, and also, despite the obvious, considering that life and death are the bases of bioethics and both must be maximized and be of good quality, the sociopolitical reasons why, from the philosopher’s point of view, it is valid to take one’s own life are examined here. In order to achieve the above, the following sections are developed: I. Bases of bioethics: good living and good dying. II. Sociopolitical reasons for dying. III. Final conclusions.